Chapter Tavola rotonda - Ciriacono, Salvatore (Datini Studies in Economic History, 2022)
Although the LII Week adequately developed the theme of Fashion in its economic, productive and technological aspects, not forgetting the expectations of consumers and the role of raw materials available over the centuries considered, other aspects of this complex issue inevitably remained on the sidelines, which refers to questions of a sociological, linguistic, psychological and even psychoanalytic nature. It would have been equally appropriate to compare, in a more direct way, what was happening in northern Europe with respect to Mediterranean Europe, bearing in mind the role of Protestantism, very far from clothing that was too flashy. The role of colors and themes, also of an artistic nature, that transpired from clothing also refer to other aspects that will have to be taken up on other occasions.